Assessing the agreement and reliability of Magene ® for heart rate monitoring - Mila Alves Matos Rodrigues; Thiago Danillo Silva; Jessika Teodoro Santos; Vinnycius Nunes de Oliveira; Nicolas Evangelista Marques; João Victor Rosa de Freitas; Marilia Santos Andrade; Rodrigo Luiz Vancini; Beat Knechtle; Katja Weiss; Ricardo Borges Viana; Claudio Andre Barbosa de Lira (Proceedings of the Institution of Mechanical Engineers, Part H: Journal of Engineering in Medicine, 2026)
To evaluate the accuracy and reliability of the Magene ® heart rate (HR) monitor compared to the Polar ® H7 (validated device) during rest, maximal graded exercise test, and active recovery. A within-group study was conducted with 68 healthy adults (21 women). Participants completed two laboratory sessions using both monitors in random order. HR values were collected at rest, during the Ellestad maximal treadmill stress testing protocol, and in active recovery. Relative reliability was assessed using the two-way random effects intraclass correlation coefficient for agreement (ICC(2,1)). Absolute reliability was assessed using typical error (TE, in bpm and %), coefficient of variation (CV, %), and minimal detectable change (MDC, in bpm and %). Agreement was examined using Wilcoxon signed-rank tests, Bland–Altman plots, and Pearson’s r or Spearman’s rho, as appropriate. No significant HR differences were found between devices ( p > 0.05). Mean biases, calculated as Polar – Magene, were 1.421 bpm at rest, 0.659 bpm during exercise, 0.103 bpm at maximal effort, and 0.569 bpm during active recovery. ICC(2,1) values ranged from 0.656 (rest) to 0.881 (maximal effort). TE ranged from 3.784 bpm (2.0%) to 6.470 bpm (8.7%), and MDC from 10.5 bpm (5.6%) to 17.9 bpm (24.2%), depending on the condition. Correlations ranged from 0.682 to 0.881. The Magene ® shows acceptable agreement with Polar ® H7 during exercise but may lack precision for resting HR monitoring in clinical settings.